Quantification of trehalose in biological samples with a conidial trehalase from the thermophilic fungus Humicola grisea var. thermoidea - Neves, M.J; Terenzi, H.F; Leone, F.A; Jorge, J.A (World journal of microbiology & biotechnology, 1994)
The partially-purified, thermally-stable trehalase from conidia of Humicola grisea was highly specific for trehalose and was free of potentially interfering activities. The enzyme was fully stable when stored in solution at -15°C for at least 6 months. This preparation could be used to quantify trehalose from 0.05 to 1.25 μmol/ml either in carbohydrate mixtures or in complex biological materials.